Energy supply security in Germany can be guaranteed even without natural gas from Russia: Special issue on the war in Ukraine - Franziska Holz; Robin Sogalla; Christian R. von Hirschhausen; Claudia Kemfert (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
The Russian war on Ukraine and Germany's dependence on Russian gas require a rethink of German energy supplies. While there is a heated debate about an immediate energy embargo, Russia could also stop its supplies at any time. To date, Germany has purchased around 55 percent of its natural gas from Russia. DIW Berlin has developed scenarios for how the German energy system could become independent of these imports as quickly as possible in the European context: On the supply side, deliveries from other natural gas exporting countries could compensate for some of the Russian exports. Security of supply would be significantly strengthened if the pipeline and storage infrastructure were used more efficiently. On the demand side, there is a short-term savings potential of 19 to 26 percent of current natural gas demand. In the medium term, a push towards renewable heat supply and higher energy efficiency is particularly necessary. If the energy-saving potential is exploited to the maximum and supplies from other natural gas supplier countries are expanded as far as technically possible at the same time, Germany's supply of natural gas will be secure in 2022 and in the coming winter 2022/2023, even without Russian imports.
Keywords: 330